BLANKETS: a toasty tool to improve social history documentation for our older patients. Issue 1161 (21st July 2021) - Warner, Bronwen E; Millar, Kate; Bolland, Mhairi; McNicholas, Jackie; Dani, Melanie
Abstract: A thorough social history is an important component of all medical clerkings and is particularly crucial when admitting an older patient. Standards exist to guide the social history content but are rarely referenced in practice. This quality improvement project conceived and implemented the novel BLANKETS (Bladder and bowels, Legal arrangements, Activities of daily living, Neurology (cognition), Kit (dentures, hearing or visual aids), EtOH and smoking, Trips, walking aids and exercise tolerance, Setup at home) tool for social history documentation, derived from existing standards, at a specialist medical inpatient hospital setting. Over a 15-week period with two cycles of intervention involving 125 patients in total, there was good staff engagement and overall improvement in social history documentation with 194/403 (48.1%) vs 199/545 (36.5%) criteria met overall and on average 6.3/13 vs 4.7/13 criteria documented for each patient. The social history BLANKETS tool is a memorable acronym to prompt clerking doctors to take a thorough and focused social history which is intrinsic to determining appropriate rehabilitation goals for effective discharge planning and setting appropriate ceiling of care decisions.